Melon/cowpea intercropping pattern influenced the N and C soil cycling and the abundance of soil rare bacterial taxa - Cuartero, Jessica; Pascual, Jose Antonio; Vivo, Juana-María; Özbolat, Onurcan; Sánchez-Navarro, Virginia; Weiss, Julia; Zornoza, Raúl; Martínez-Mena, María; García, Eloisa; Ros, Margarita (Frontiers in Microbiology, 2022)
The high use of pesticides, herbicides, and unsustainable farming practices resulted in losses of soil quality. Sustainable farming practices such as intercropping could be a good alternative to traditional monocrop, especially using legumes such as cowpea (Vigna unguiculata L. Walp). In this study, different melon and cowpea intercropping patterns (melon mixed with cowpea in the same row (MC1); alternating one melon row and one cowpea row (MC2); alternating two melon rows and one cowpea row (MC3)) were assayed to study the intercropping effect on soil bacterial community through 16S rRNA region in a 3-year experiment. The results indicated that intercropping showed high content of total organic carbon, total nitrogen and ammonium, melon yield, and bacterial diversity as well as higher levels of beneficial soil microorganisms such a Pseudomonas, Aeromicrobium, Niastella, or Sphingomonas which can promote plant growth and plant defense against pathogens. Furthermore, intercropping showed a higher rare taxa diversity in two (MC1 and MC2) out of the three intercropping systems. In addition, N-cycling genes such as nirB, nosZ, and amoA were more abundant in MC1 and MC2 whereas the narG predicted gene was far more abundant in the intercropping systems than in the monocrop at the end of the 3-year experiment. This research fills a gap in knowledge about the importance of soil bacteria in an intercropping melon/cowpea pattern, showing the benefits to yield and soil quality with a decrease in N fertilization.